2019
DOI: 10.1016/j.jsv.2019.114904
|View full text |Cite
|
Sign up to set email alerts
|

A spectral collocation method for acoustic scattering by multiple elastic plates

Abstract: This paper presents a new approach to solving acoustic scattering problems: the Unied Transform method. This spectral, boundary-based collocation method can be readily applied to acoustic scattering by disjoint two-dimensional structures, and, for the purposes of this paper, is illustrated in the case of multiple at plates, which also addresses the additional diculty of mathematical singularities in the scattered eld due to diraction at sharp edges. Fluid-structure interaction may also be incorporated into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…where a constant stiffness has been chosen so that we were able to validate the results with the methods of [9]. We consider a plane wave incident field of angle π/4 and k 0 = 10.…”
Section: Extension To Multiple Platesmentioning
confidence: 99%
“…where a constant stiffness has been chosen so that we were able to validate the results with the methods of [9]. We consider a plane wave incident field of angle π/4 and k 0 = 10.…”
Section: Extension To Multiple Platesmentioning
confidence: 99%
“…Dzieciuch wrote the first code for the normal mode model approximated by Chebyshev polynomials [ 17 ]. In 2019, Colbrook et al used the boundary-based collocation spectral method to solve the two-dimensional acoustic scattering problem [ 18 ]. In the same year, Wise et al used the Fourier spectral collocation method to solve the distribution of sound sources.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal in this article is to extend this analysis to linked boundary conditions. A key tool in our analysis is the unified transform (also known as the Fokas method), a novel transform for analyzing boundary value problems for linear (and integrable nonlinear) partial differential equations (PDEs) 7–19 . An excellent pedagogical review of this method can be found in the paper of Deconinck et al 20 …”
Section: Introductionmentioning
confidence: 99%